THE STUDENTS’ LEARNING STRATEGIES IN ACHIEVING ACADEMIC PERFORMANCE OF HIGHER TOEFL SCORES - Regina Rahmi; Mulyani; Effendi (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research is intended to find out the learning strategies that Respondents used to get higher TOEFL scores. TOEFL is test of English as foreign language, or a standardize in measuring the abilities in English skills (Listening, Structure and Reading). This research used samples method by using qualitative approach. In this study, the writer found the respondents who got higher TOEFL scores. Then, the writer asked each of the respondent about the strategy that made their scores higher in TOEFL test. This research used both interview and questionnaire instruments. The interview was 10 questions about the TOEFL learning strategies, and the respondents answered relate to their strategy used in learning TOEFL. In addition, the writer made a questionnaire instrument in the research aimed to find out the TOEFL learning strategies scales that respondents usually applied in learning TOEFL. Moreover, The interview and the questionnaire showed that the strategies that respondents used in learning TOEFL was a proper methods to apply in learning TOEFL. In this research, the dominant strategy relate to the theory respondents used, were the audiotory and visual methods, the respondents used those because the TOEFL is the language testing, so visual and audiotory were very influential in learning learning TOEFL. In conclusion, the research illustrated that learning TOEFL has each strategy depends on the respondent, and the strategy that respondents used have been increased their TOEFL scores in official test.